Penjadwalan Produksi Menggunakan Metode Economic Production Quantity (EPQ) (Studi Kasus: CV. Kopi Biji Palembang) - Saputra, Pajri Dwi; Hardini, Septa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of the Economic Production Quantity (EPQ) method in scheduling ground coffee production at CV Kopi Biji Palembang. A quantitative approach was employed using primary data from observations and interviews and secondary data from production documents. The EPQ model considers annual demand, setup cost, holding cost, and production rate. Results show that the optimal production quantity is 39,683 kg per cycle, with three production runs annually. This significantly reduces inventory costs and minimizes the risks of overstocking and stockouts. The EPQ implementation improves operational efficiency and capacity utilization. This study recommends adjusting the cycle during seasonal demand peaks.